Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1038/5056
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase expression in human somatic cells does not induce changes associated with a transformed phenotype

Abstract: Expression of the human telomerase catalytic component, hTERT, in normal human somatic cells can reconstitute telomerase activity and extend their replicative lifespan. We report here that at twice the normal number of population doublings, telomerase-expressing human skin fibroblasts (BJ-hTERT) and retinal pigment epithelial cells (RPE-hTERT) retain normal growth control in response to serum deprivation, high cell density, G1 or G2 phase blockers and spindle inhibitors. In addition, we observed no cell growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
361
4
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 595 publications
(388 citation statements)
references
References 22 publications
(22 reference statements)
19
361
4
4
Order By: Relevance
“…Some authors have noted that hTERT þ cells express a normal cell-cycle arrest and checkpoint protein response to specific challenges including DNA damaging agents (including chromium) (Jiang et al, 1999;Morales et al, 1999;Pritchard et al, 2001;Wood et al, 2001;Gorbunova et al, 2002). In contrast, other authors have reported that there is a loss of p16INK4a and hyperphosphorylation of pRb in hTERT þ cells (Tsutsui et al, 2002;Piboonniyom et al, 2003) and in one cell line a mutation in p53 and abnormal G1 checkpoint (Noble et al, 2004).…”
Section: Metal-induced Genomic Instabilitymentioning
confidence: 99%
“…Some authors have noted that hTERT þ cells express a normal cell-cycle arrest and checkpoint protein response to specific challenges including DNA damaging agents (including chromium) (Jiang et al, 1999;Morales et al, 1999;Pritchard et al, 2001;Wood et al, 2001;Gorbunova et al, 2002). In contrast, other authors have reported that there is a loss of p16INK4a and hyperphosphorylation of pRb in hTERT þ cells (Tsutsui et al, 2002;Piboonniyom et al, 2003) and in one cell line a mutation in p53 and abnormal G1 checkpoint (Noble et al, 2004).…”
Section: Metal-induced Genomic Instabilitymentioning
confidence: 99%
“…However, we and others have described earlier that the only step required for the immortalization of somatic cells is activation of telomerase (Jiang et al, 1999;Morales et al, 1999;Li et al, 2007). In our study, we generated hTERT immortalized epithelial cell lines without disruption of pRb and p53 function.…”
mentioning
confidence: 90%
“…Primary dermal fibroblasts from an XP-V patient (GM3617) and a normal control (GM5659D) were immortalized with the catalytic subunit of telomerase (hTERT) which does not disrupt normal cell cycle checkpoints [30][31][32] [33] and cells were designated GM5659DT and GM3617T. We employed a gene knockdown approach using RNA interference directed against a target sequence of p53 [29].…”
Section: P53-suppressed Xp-v and Normal Fibroblasts[30]mentioning
confidence: 99%